Investigating the electrohydrodynamic effect (EHDE) for macroscopic actuation - Soh, Cher Yee (2018)
This is the thesis written by the author in fulfilment of his Final Year Project (FYP) requirement for Bachelor of Engineering (Electrical and Electronics Engineering) for Academic Year (AY) 17/18. The purpose of this thesis is to examine of the electrohydrodynamic Effect (EHDE) for macroscopic actuation, for the phenomenon that is explained through literature review and theories. The thesis is broken down into 3 main portion- namely the calculation, the simulation and the experiment. For the calculation, it is to tabulate the results of different formula in plotting on graphs to see the variation of factor and how it will affect the end result. For the simulation, it is to see if the concept of electric field, the outcome it is as expected of having a non-uniform electric field. Lastly, the experiment will further enhance and validate the previous two steps taken.